Critical organizational success factors for public private partnership projects – a comparison of solicited and unsolicited proposals - Yun, Sungmin; Jung, Wooyong; Han, Seung Heon; Park, Heedae (Journal of Civil Engineering and Management, 2015)
Public Private Partnership (PPP) projects are typically initiated through solicited or unsolicited proposals. The difference between the processes according to the proposal mode often leads to different levels of involvement and responsibilities for the public and private sectors. However, no robust research exists to capture the differences, depending on the proposal mode, in the roles and involvement of project participants and the impact of those differences on project success. This study intends to explore the critical organizational success factors contributing to the success of PPP projects according to the proposal mode and to provide practical recommendations for project success from organizational perspectives. To assess the factors, 141 questionnaire surveys were conducted with participants in 32 PPP projects. The major findings indicated that “Project Implementation Capability” had the most critical influence on solicited projects, whereas “Risk Sharing and Mitigation Strategies” was the most significant in unsolicited projects. In addition, “Interorganization Coordination” among project participants was essential to the success for both solicited and unsolicited projects. Government roles and involvement were also critical, although their contributions were relatively less important than other critical organizational success factors. Based on the findings, practical recommendations were provided for the success of solicited and unsolicited projects.